Left atrial reservoir strain and long-term prognosis in patients with heart failure and reduced ejection fraction. (3rd October 2022) - Chimed, S; Stassen, J; Galloo, X; Meucci, M C; Van Der Bijl, P; Marsan, N A; Delgado, V; Bax, J J
Abstract: Background: Cardiac damage in heart failure (HF) with reduced ejection fraction (HFrEF) often involves structural and functional left atrial (LA) abnormalities. Speckle-tracking echocardiography derived LA reservoir strain (LARS) is a sensitive measurement for early detection of LA dysfunction. However, the prognostic value of LARS is not well established in patients with HFrEF. Methods: LARS was measured with speckle tracking echocardiography in patients who had a first echocardiographic diagnosis of reduced LVEF (≤45%). Patients with prior history of atrial fibrillation (AF) were excluded. The primary endpoint was newly onset AF, while the composite endpoint of newly onset AF and all-cause mortality was chosen as the secondary endpoint. The study population was divided into two groups according to the optimal threshold value of baseline LARS (derived from spline curve analysis) (Figure 1) and event-free survival rates were compared by the Kaplan-Meier method. Results: A total of 997 patients (mean age 62±13 years, 73% men) were analyzed. At baseline, LA volume index was significantly larger (41±17 vs. 32±12 ml/m 2, p<0.001), and LA reservoir function significantly more impaired (9±3.1 vs. 21±6.3%, p<0.001) in patients with LARS ≤14% compared to patients with LARS >14%. During a median follow-up of 60 months (interquartile range [IQR] 29–60 months), newly onset AF occurred in 75 patients (7.5%), while 254 patients (25.5%) experienced the composite endpoint of newly onset AF and all-cause mortality. The 5-year event-free survival rates for both endpoints were significantly lower in the LARS ≤14% group compared to LARS >14% group (Figure 1A for new onset AF and Figure 2B for the composite endpoint of newly onset AF and all-cause mortality). After adjustment for important risk factors, including HF treatments and echocardiographic predictors, baseline LARS remained independently associated with a higher risk of development of AF (HR=0.89, 95% CI 0.85–0.94, p<0.001) and the composite of newly onset AF and all-cause mortality (HR=0.93, 95% CI 0.91–0.96, p<0.001). Conclusions: Baseline LARS is associated with long-term prognosis in patients with HFrEF and the association is independent from various clinical and echocardiographic predictors. Funding Acknowledgement: Type of funding sources: None.